2016
DOI: 10.5152/iao.2016.2682
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 4-Week Treatment with Cilostazol in Patients with Chronic Tinnitus: A Randomized, Prospective, Placebo-controlled, Double-blind, Pilot Study

Abstract: OBJECTIVE:The aim of this prospective, double-blind, randomized, placebo-controlled study was to evaluate the efficacy of cilostazol, a selective phosphodiesterase 3 inhibitor, in patients with chronic tinnitus. MATERIALS and METHODS:Adult patients of chronic tinnitus lasting more than 3 months were included. Fifty eligible patients were randomly assigned to either cilostazol or control (placebo) group. The study medication of oral 100-mg cilostazol and a matching placebo were used twice a day for 4 weeks. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
1
Order By: Relevance
“…One study explored the efficacy of cilostazol in chronic tinnitus, and reported some improvement (108).…”
Section: Pde3 Inhibitorsmentioning
confidence: 99%
“…One study explored the efficacy of cilostazol in chronic tinnitus, and reported some improvement (108).…”
Section: Pde3 Inhibitorsmentioning
confidence: 99%
“…Com relação à influência do gênero no predomínio da queixa de zumbido, os achados na literatura são controversos, tendo sido verificado em alguns estudos a prevalência do gênero masculino 21 e em outros do gênero feminino 7,22 . Entretanto, dificilmente as diferenças entre os gêneros são estatisticamente significativas.…”
Section: Discussionunclassified
“…Such types of 11-point VASs are often used as measures for pain, 33 , 34 and have also been found useful for the assessment of other unpleasant and distressing symptoms, such as dizziness 35 or tinnitus. 33 , 36 , 37 In the studies reviewed here, 11-point box scales for tinnitus and dizziness were administered with the extreme ends indicating “no tinnitus at all” (0) and “extremely severe tinnitus” (10) or “no dizziness at all” (0) and “extremely severe dizziness” (10).…”
Section: Methodsmentioning
confidence: 99%